Effectiveness of nonviolent communication (NVC) workshop on marital adjustment (Dhaka University Journal of Biological Sciences, 2017)
The present study examined the effectiveness of nonviolent communication (NVC) workshop on marital adjustment. The hypothesis was receiving nonviolent communication (NVC) workshop has positive impact on marital adjustment. The independent variable was NVC workshop and the dependent variable was marital adjustment score. For conducting this research, repeated measures design was followed and 20 Bangladeshi married people participated in it. The results have shown that there was a statistically significant difference (F = 16.790, p < 0.05) in marital adjustment score of experimental group over the three time periods and pairwise comparisons indicate that there was significant difference between pretest and post-test and also between pretest and follow- up test at the 0.05 level. Results also have shown that, there was statistically significant difference of marital adjustment score between experimental and control group in posttest (t = 4.276, p < 0.05) and follow-up test (t = 4.176, p < 0.05). Thus, after receiving NVC workshop the marital adjustment score of experimental group increased significantly (F = 16.79, p < 0.001) in post-test measure and also remain constant in follow-up, whereas the marital adjustment score of control group had no significant change. This implied a significant positive impact of participation in NVC workshop on marital adjustment.Dhaka Univ. J. Biol. Sci. 26(1): 69-75, 2017 (January)